PENERAPAN NFCM DALAM PEMBELAJARAN DARING UNTUK MENINGKATKAN HASIL BELAJAR MATERI BENTUK MOLEKUL - mus indriana (Gema Pendidikan, 2021)
Shape of molecule is material that is abstract or cannot be seen directly. That's why this material requires a model to be observed directly. It is feared that online learning will increase the difficulty level of understanding this material. The purpose of this classroom action research is to find out that NFCM in online learning can improve learning outcomes in shape of molecule material for class X MIPA 6 students of SMAN 1 Gresik during the Covid-19 pandemic. This research is a classroom action research which takes place in 3 cycles. The results showed that the percentage of learning completeness, the average test score for each cycle, and the activeness of students in each cycle increased from cycle to cycle. Based on these results it can be concluded that the application of NFCM in class X MIPA 6 SMAN 1 Gresik has succeeded in increasing student learning outcomes in shape of molecule material. Because of this success NFCM can be applied to other materials or other classes during this online learning.